The strategist be the leader your business needs - Montgomery, Cynthia A. (New York Harper Business, 2012)
Based on an acclaimed professor's legendary strategy course at Harvard Business School, The Strategist offers a radically new perspective on a leader's most vital role.
Includes bibliographical references and index.
Keywords: Leadership